Neonatal handling decreases unconditioned anxiety, conditioned fear, and improves two-way avoidance acquisition: a study with the inbred Roman high (RHA-I)- and low-avoidance (RLA-I) rats of both sexes - Río-Alamos, Cristobal; Puigdellivol, Ignasi O.; Cañete, Antoni; Blazquez, Gloria; Martinez-Membrives, Esther; Tobeña, Adolf; Fernandez-Teruel, Alberto (Frontiers in Behavioral Neuroscience, 2015)
The present study evaluated the long-lasting effects of neonatal handling (NH; administered during the first 21 days of life) on unlearned and learned anxiety-related responses in inbred Roman High- (RHA-I) and Low-avoidance (RLA-I) rats. To this aim, untreated and neonatally-handled RHA-I and RLA-I rats of both sexes were tested in the following tests/tasks: a novel object exploration (NOE) test, the elevated zero maze (ZM) test, a “baseline acoustic startle” (BAS) test, a “context-conditioned fear” (CCF) test and the acquisition of two-way active—shuttle box—avoidance (SHAV). RLA-I rats showed higher unconditioned (novel object exploration test -“NOE”-, elevated zero maze test -“ZM”-, BAS), and conditioned (CCF, SHAV) anxiety. NH increased exploration of the novel object in the NOE test as well as exploration of the open sections of the ZM test in both rat strains and sexes, although the effects were relatively more marked in the (high anxious) RLA-I strain and in females. NH did not affect BAS, but reduced CCF in both strains and sexes, and improved shuttle box avoidance acquisition especially in RLA-I (and particularly in females) and in female RHA-I rats. These are completely novel findings, which indicate that even some genetically-based anxiety/fear-related phenotypes can be significantly modulated by previous environmental experiences such as the NH manipulation.